Reliability and Validity of the German Version of the Emotional Style Questionnaire - Jekauc, Darko; Mülberger, Lea; Weyland, Susanne; Ennigkeit, Fabienne; Wunsch, Kathrin; Krell-Roesch, Janina; Fritsch, Julian (Frontiers in Psychology, 2021)
Until recently, emotional processes have played little role in personality psychology. Based on neuroscientific findings, Davidson and colleagues proposed a theory of emotional styles, postulating six dimensions of emotional life: outlook, resilience, social intuition, self-awareness, sensitivity to context, and attention. Recently, an English version of the Emotional Style Questionnaire (ESQ) was developed and tested for reliability and validity. The aim of the present work was to test the test-retest reliability, internal consistency, construct validity, and criterion validity of the German version of the ESQ. Two separate samples consisting of 365 and 344 subjects took part in an online survey. The results of the two studies indicated satisfactory test-retest reliability and internal consistency. Regarding the construct validity, the results from Study 1 and Study 2 indicate good model fit indices. Although there was a high correlation between the subscales outlook and resilience, the analyses supported the six-factor structure postulated by Davidson and colleagues. Substantial correlations were found between the dimensions of the ESQ and other validated scales, confirming the criterion validity of the questionnaire. Our results suggest that the German version of the ESQ is a reliable and valid measurement of emotional styles. It is a feasible and economical questionnaire that can be applied in various psychology disciplines, such as personality psychology, clinical psychology, industrial psychology or sport and exercise psychology.